Laboratory designed hot mix asphalt mixtures with post-consumer Recycled Asphalt Shingles (RAS) utilizing AASHTO PP78. (30th November 2019) - Haas, Edwin; Ericson, Christopher L.; Bennert, Thomas
Highlights: Asphalt shingles are recycled into asphalt to reduce both material demands and cost. DOTs allow for the use of shingles into their asphalt at low percentages by weight. Inclusion of RAS was evaluated for liquid and mixture performance testing. Abstract: Historically, many state Departments of Transportation (DOTs) do not allow the use of post-consumer Recycled Asphalt Shingles (RAS) due to the high probability that they would be contaminated with asbestos. This study evaluates the performance of hot mix asphalt designed with post-consumer waste RAS provided by local supplier in Bethlehem, PA. Many construction debris recycling plants have a method to ensure their processed post-consumer shingles do not contain asbestos, making it a viable material for inclusion into asphalt pavements. AASHTO PP78, Standard Practice for Design Considerations When Using Reclaimed Asphalt Shingles (RAS) in Asphalt Mixtures, was used in the study in order to design the asphalt mixtures containing the RAS addition. This design method was developed to take into consideration the stiffness of the RAS asphalt binder to help reduce the potential for fatigue cracking. The results of the testing regiment provide guidance to local, state, and federal agencies as to the impacts of including RAS into asphalt pavements and whether to allow post-consumer waste RAS in HMA. However, the issue with utilizing this type of "substitution" specification is that it does not take into the account the quality of the asphalt binder of the RAS. AASHTO PP 78 evaluates the quality of the RAS binder, blended with the virgin asphalt binder, by recommending the solvent recovery of the RAS asphalt binder, blending it with the virgin asphalt binder at varying percentages, and then determining the asphalt binder properties – in particular the influence on the PG grade and the difference in the low temperature critical cracking temperatures (ΔTC ).